Reliable Prognostic Cardiopulmonary Function Variables in 110 Patients With Acute Ischemic Heart Disease - Jeong Jae Lee; Chan-hee Park; Joshua (Sung) (Korean Research Society of Physical Therapy, 2022)
Background: The oxygen uptake efficiency slope (OUES) is the most important index for accurately measuring cardiopulmonary function in patients with acute ischemic heart disease. However, the relationship between the OUES variables and important cardiopulmonary func-tion parameters remain unelucidated for patients with acute ischemic heart disease, which accounts for the largest proportion of heart disease.Objects: The present cross sectional clinical study aimed to determine the multiple relation-ships among the cardiopulmonary function variables mentioned above in adults with acute ischemic heart disease.Methods: A convenience sample of 110 adult inpatients with ischemic heart disease (age: 57.4 ± 11.3 y; 95 males, 15 females) was enrolled at the hospital cardiac rehabilitation center. The correlation between the important cardiopulmonary function indicators including peak oxygen uptake (VO2 peak), minute ventilation (VE)/carbon dioxide production (VCO2) slope, heart rate recovery (HRR), and ejection fraction (EF) and OUES was confirmed.Results: This study showed that OUES was highly correlated with VO2 peak, VE/VCO2 slope, and HRR parameters.Conclusion: The OUES can be used as an accurate indicator for cardiopulmonary function. There are other factors that influence aerobic capacity besides EF, so there is no correlation with EF. Effective cardiopulmonary rehabilitation programs can be designed based on OUES during submaximal exercise in patients with acute ischemic heart disease.